CULTURAL PREJUDICE AND GENERATIONAL GAPS: BARRIERS TO ACCESSING BUDDHIST PSYCHOLOGICAL TREATMENT - LE VAN TRUC; Thanasak, Pontappasarn; Chiyaphan, Thanad (Journal of Contemporary Buddhist Society = JCBS, 2026)
Mental health within the Vietnamese community, encompassing both local citizens and Vietnamese immigrants residing in the United States, remains significantly stigmatized due to deeply rooted cultural beliefs, traditional belief systems, and significant intergenerational disparities in mental health literacy and acceptance. This article examines the anthropological, cultural, and psychological dimensions of these barriers, exploring how mental illness is often mischaracterized as a sign of personal weakness, moral failure, severe insanity, or the karmic consequence of past wrongdoing. Older generations, driven by collectivist imperatives to preserve family honor and a pervasive fear of community judgment, routinely dismiss psychological distress and actively resist professional psychological treatment. Younger generations, shaped by contemporary education and greater exposure to global mental health discourse, demonstrate considerably greater openness toward acknowledging and addressing mental health difficulties, yet remain constrained by familial expectations, intergenerational conflict, and the emotional invalidation of their struggles by elders. These cultural and generational disparities create significant barriers to accessing necessary psychological care, resulting in widespread silent suffering that exacerbates individual distress and undermines community well-being. To bridge this divide effectively, this article argues for the integration of Buddhist psychological principles particularly the Brahmavihara of loving-kindness (Metta) and compassion (Karuna) into culturally competent mental health practice. By framing psychological intervention within Buddhist contemplative traditions that are already deeply embedded in Vietnamese cultural identity, practitioners can destigmatize treatment, cultivate empathic understanding across generations, and encourage help-seeking behaviors among vulnerable populations. Furthermore, the synergistic application of mindfulness and forgiveness practices is examined as a mechanism for fostering social cohesion in multicultural environments, with evidence drawn from research conducted in Binh Duong province, Vietnam. The article concludes that culturally sensitive, Buddhist-informed interventions offer a viable and transformative pathway toward healing individual trauma, repairing intergenerational relationships, and building resilient, harmonious communities.